Longitudinal analyses of infants’ microbiome and metabolome reveal microbes and metabolites with seemingly coordinated dynamics - Hao Wu; Douglas V. Guzior; Christian Martin; Kerri A. Neugebauer; Madison M. Rzepka; Julie C. Lumeng; Robert A. Quinn; Gustavo de los Campos (Communications Biology)
Abstract Population studies have shown that the infant’s microbiome and metabolome undergo significant changes in early childhood. However, no previous study has investigated how diverse these changes are across subjects and whether the subject-specific dynamics of some microbes correlate with the over-time dynamics of specific metabolites. Using mixed-effects models, and data from the ABC study, we investigated the early childhood dynamics of fecal microbiome and metabolome and identified 83 amplicon sequence variants (ASVs) and 753 metabolites with seemingly coordinated trajectories. Enrichment analysis of these microbes and molecules revealed eight ASV families and 23 metabolite groups involving 1032 ASV-metabolite pairs with their presence-absence changing in a coordinated fashion. Members of the Lachnospiraceae (464/1032) and metabolites related to cholestane steroids (309/1032) dominated proportional shifts within the fecal microbiome and metabolome as infants aged.